Manejo de los ejercicios aeróbicos en estudiantes con discapacidad auditiva en el bachillerato de la Unidad Educativa Profesor Francisco Terán, Cantón Vinces, Parroquia Antonio Sotomayor, Recinto Clarisa Provincia de Los Ríos, periodo, abril- septiembre, 2022 - Peralta Morante, José Miguel (2022)
The present research work will be carried out prior to obtaining the degree of licensed teacher in Pedagogy of Physical Activity and Sport under the theme called "management of aerobic exercises in students with hearing disabilities", it was carried out in order to determine the influence of aerobic exercises in high school students in the Professor "Francisco Terán" Educational Unit, having as a line of research the Pedagogy of Physical Activity and Sport "offered by the faculty, , the search for information is not experimental, but if descriptive, where the case study variables are located, which are explored and subsequently described, where analysis of aerobic exercises will be carried out in students who maintain a special educational need SEN (hearing), a quantitative design is also followed for the measurement of the data, which will be duly collected and classified in the Educational Unit of Clariza, p For which there is a population and sample composed of 22 members in which a series of questions was distributed to the physical education teacher, the students, and the parents, which concluded that the physical education teacher knows the qualities of comprehensive management with students with hearing disabilities, but it is difficult to control them, on many occasions.